(untitled) (Research, Society and Development, 2021)
This manuscript aims to report the experience of a mental health resident, who worked in health care and health management spaces, discussing situations of judicialization of child and adolescent care. It is understood that their compulsory hospitalization is a matter of paramount importance due to the increase in cases and to elucidate care flows. It is a qualitative, transversal and exploratory report, whose instruments were field diaries and participant observation. The writing will deal with the experience of the resident itself, without describing services or professionals in those spaces. The perceptions signal the importance of continuing education on the subject, and consequent constant qualification of professionals who work both in care and in health management. The high number of hospitalizations of children and adolescents is noticeable, especially those who have already experienced serious violations of human rights and/or use psychoactive substances, even in non-abusive situations. The low articulation between the care actors, as well as the difficulty in adhering to the care proposed to them, is still an unresolved aggravating factor, reflecting on the judicialization of infants and young people. Therefore, the importance of residency lies in its training strategy for professionals who will seek to work in public health and for those who already do so. The resident’s role is evidenced in the potentialization of theoretical discussions that are combined with those techniques, promoting critical reflections with participatory analysis, realizing inconsistencies and contradictions in the implementation of public care policies.